A Facile Green Fabrication and Characterization of Cellulose-Silver Nanoparticle Composite Sheets for an Antimicrobial Food Packaging - Kwon, Seongyoung; Lee, Wooseok; Choi, Jung Wook; Bumbudsanpharoke, Nattinee; Ko, Seonghyuk (Frontiers in Nutrition, 2021)
The present study focused on a facile and green approach for the one-step synthesis of silver nanoparticles (AgNPs) embedded in hard wood bleached kraft fiber. The hydroxyl groups on the cellulose chain induced ionic silver reduction with additional hydrothermal energy, allowing for the in situ formation and deposition of AgNPs on the cellulose fiber. The white color of the bleached fiber transformed to yellow due to the formation of AgNPs. UV-Vis spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy revealed that the AgNPs were uniformly distributed across the surface of the obtained cellulose fibers. The results indicated that the formation and distribution of AgNPs on surface of cellulose fibers was significantly influenced by the amount and concentration of silver nitrate (AgNO3). The antimicrobial activity of the cellulose-AgNP composite sheet against Escherichia coli was found to be inhibiting. These findings imply that cellulose-AgNP composite sheets can be feasibly used as antimicrobial paper for food packaging.